1997
DOI: 10.1259/bjr.70.829.9059292
|View full text |Cite
|
Sign up to set email alerts
|

Do non-specific minimal signs in a biennial mammographic breast cancer screening programme need further diagnostic assessment?

Abstract: Abstract. Mammographic features such as small vague densities, indefinable microct subtle architectural distortions, alone or in combination, are non-specific appearances ior breast cancer. These features sometimes precede malignancy and a decisive strategy on how to deal with non-specific minimal signs in a breast cancer screening programme is studying the prevalence of these signs in a Dutch Breast Cancer Screening Centre and estimating the risk of participants with these signs acquiring breast cancer within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 8 publications
2
19
0
Order By: Relevance
“…However, these diVerences were too small to be useful in improving screening sensitivity. Therefore we, as others previously, 50 were unable to identify any specific lesions particularly indicative of subsequent poor prognosis.…”
Section: Figure 4 Risk Group Given Appearance Of Lesions (A) On Screementioning
confidence: 54%
“…However, these diVerences were too small to be useful in improving screening sensitivity. Therefore we, as others previously, 50 were unable to identify any specific lesions particularly indicative of subsequent poor prognosis.…”
Section: Figure 4 Risk Group Given Appearance Of Lesions (A) On Screementioning
confidence: 54%
“…Per Skaane in the Oslo II study at a recall rate of 3.7% for digital and 3.0% for film-screen mammography (compared to around 10% for women <50 years of age in the DMIST trial) found a much smaller, statistically not significant advantage for digital mammography in women below the age of 50 ( Table 2). To be able to take full advantage of digital mammography in women with dense breasts, it may therefore be necessary to aggressively recall even subtle findings, so-called "minimal signs" as defined in the Dutch screening program [43]. In European populationbased screening programs, however, there is a tendency to initially ignore these minimal signs in order to keep the recall rate at an acceptable low level [43].…”
Section: Clinical Comparison Of Digital and Film-screen Mammographymentioning
confidence: 99%
“…To be able to take full advantage of digital mammography in women with dense breasts, it may therefore be necessary to aggressively recall even subtle findings, so-called "minimal signs" as defined in the Dutch screening program [43]. In European populationbased screening programs, however, there is a tendency to initially ignore these minimal signs in order to keep the recall rate at an acceptable low level [43]. …”
Section: Clinical Comparison Of Digital and Film-screen Mammographymentioning
confidence: 99%
“…Inclusion criteria were nonpalpable mammographic lesions in accordance with the characteristics listed in Table 1. All of these radiological criteria for potential malignancy had to appear on at least two conventional mammograms in standard projection (Sickles, 1994;Maes et al, 1997). Diffuse microcalcifications found in mammograms were eligible if accompanying risk features, such as elongated round or vermiform microcalcifications, were detected.…”
Section: Identification Of Women With Early Breast Cancer By Analysismentioning
confidence: 99%
“…Increasing knowledge of high-risk groups and regular screening mammography have resulted in an improvement in the rate of detection of smaller malignant lesions (Arnesson et al, 1995;Tabar et al, 1995). However, certain minimal mammographic features, such as small vague densities, indefinable microcalcification or subtle architectural distortions, alone or in combination, can also represent non-specific indications of cancerous lesions (Sickles, 1994;Ciatto et al, 1995;Hiatt and Pasick, 1996;Maes et al, 1997). In addition, the diagnostic accuracy of mammographic screening in women under 50 with dense breast parenchyma has been questioned by some authors (Black et al, 1995;Leitch, 1995).…”
mentioning
confidence: 99%